Cotton Sector Strategies in West and Central Africa - Goreux, Louis (IMF Working Papers; Working Paper ;, 2002)
Cotton production in West and Central Africa (WCA) has contributed to growth and poverty reduction. Recently, the objective of poverty alleviation has been adversely impacted by the downward pressures on world prices (exacerbated by subsidies by major cotton producers outside Africa). Several countries in WCA are undergoing reforms in the cotton sector to stimulate greater market competition and raise the share of the international price going to farmers. While these efforts would help to improve rural income irrespective of the world market situation, they would be more powerful in combination with a reduction in other countries' subsidies in this sector.